Ion-Selective Optical Sensors: A New Look at Well-Established Techniques of Signal Acquisition - Andrey Kalinichev; Maria Peshkova; Nadezhda Pokhvishcheva; Konstantin Mikhelson (Proceedings, 2018)
It is demonstrated for the first time that the registration of the optode signal under non-equilibrium conditions reduces analysis time and shifts the sensor working range. The fabrication of optode-like color standards for digital color analysis (DCA) is described, and a multi-parameter color scale for calibration-free sensor arrays is proposed. Advantages and limitations of monochrome and color camera for DCA with colorimetric optodes are discussed.